Hemoglobin Examination and Giving Guava Juice to Pregnant Women in Cibungbulang District, Bogor Regency: Pemeriksaan Hemoglobin dan Pemberian Jus Jambu Biji pada Ibu Hamil di Kecamatan Cibungbulang Kabupaten Bogor - Dahlan, Febry Mutiariami; Aulya, Yenny; Fetrisia, Wiwit (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
According to data from the WHO (World Health Organization), In 2017, an estimated 295,000 maternal deaths of women died during and after pregnancy and childbirth.  The Ministry of Health of the Republic of Indonesia (Kemenkes RI) recorded that the number of maternal deaths in Indonesia was 4,627 people in 2020. This number increased by 8.92% from the previous year, 4,197 people. By province, 745 mothers who died were in West Java last year. The proportion reaches 16.1% of the total maternal mortality in the country.  Anemia is one of the indirect causes of maternal death due to bleeding. In pregnant women, anemia increases the frequency of complications in pregnancy and childbirth. In general, one of the causes of iron deficiency anemia is insufficient iron intake and inadequate absorption (Widyastuti, 2005). Iron absorption is greatly influenced by the availability of vitamin C in the mother's body. Guava juice is a fruit easily and cheaply obtained by the public. Red guava contains carbohydrates of 12.2 g / 100 gr and fiber of 5.6 g / 100 guava fruit.  So, it is hoped that pregnant women will understand their condition during pregnancy after this service. This community service was conducted through demonstrations and practices on 20 pregnant women in Cibungbulang District, Bogor Regency. This activity went well, and pregnant women felt the benefits of this service activity. Pregnant women are expected to be aware of the dangers of anemia and the benefits of detection by checking hemoglobin and consuming guava juice to increase hemoglobin levels.